Norwegian society of rheumatology recommendations on diagnosis and treatment of patients with giant cell arteritis - Haaversen, Anne Bull; Brekke, Lene Kristin; Bakland, Gunnstein; Rødevand, Erik; Myklebust, Geirmund; Diamantopoulos, Andreas P. (Frontiers in Medicine, 2023)
Objective To provide clinical guidance to Norwegian Rheumatologists and other clinicians involved in diagnosing and treating patients with giant cell arteritis (GCA). Methods The available evidence in the field was reviewed, and the GCA working group wrote draft guidelines. These guidelines were discussed and revised according to standard procedures within the Norwegian Society of Rheumatology. The European Alliance of Associations for Rheumatology (EULAR) recommendations for imaging and treatment in large vessel vasculitis and the British Society for Rheumatology (BSR) guidelines for diagnostics and treatment in GCA informed the development of the current guidelines. Results A total of 13 recommendations were developed. Ultrasound is recommended as the primary diagnostic test. In patients with suspected GCA, treatment with high doses of Prednisolone (40-60 mg) should be initiated immediately. For patients with refractory disease or relapse, Methotrexate (MTX) should be used as the first-line adjunctive therapy, followed by tocilizumab (TCZ). Conclusion Norwegian recommendations for diagnostics and treatment to improve management and outcome in patients with GCA were developed.